FLORAE MALESIANAE PRECURSORES XXIII THE GENUS RHODODENDRON IN MALAYSIA - H. SLEUMER (Research Center for Biology, 1960)
In this revision of the Malaysian species of the genus Rhododendron L. 261 species and 55 varieties and forms have been distinguished, of which 96 species (some obviously hybrids) and 29 varieties are described as new; 10 species have been reduced to the rank of a variety or form, and 67 species, varieties, or forms have for the first time been regarded as synonym. In the keys to several subsections or series the extra-Malaysian species are included.